Avaliação da prevalência de anomalias dentárias associadas à agenesia de segundos pré-molares - Gomes, Simone Carinhena (2007)
Studies had suggested one high correlation between agenesis of second premolar with other agenesis and dental anomalies. It seems to have a genetic interrelation in the determination of anomalies, being considered the high frequency of associations. The objective of this study were to evaluate in patients with agenesis of second premolar the prevalence of other agenesis and anomalies such as related with position, form, size and to compare with the prevalence of these anomalies waited for the population in general. Due to perform this comparison, a composed sample for documentations of 203 patients from 8 to 22 years old was selected presenting agenesis of at least one second premolar. The sample was collected from the examination of the pertaining orthodontic documentation to the archive of a University, a particular school of specialization and 8 doctor's offices. The study material included periapicais x-rays, panoramic x-rays, study model and clinical promptuary of the patients. By means of the examination of this material the following information had been registered: age of the patient, sex and etnia; descriptions of permanent tooth extractions; presence of other dental anomalies associates including itself agenesis of other permanent teeth, ectopias of teeth unerupted, transpositions, infra-occlusion of the second molar deciduous remainders, microdontia of lateral incisor maxillary and mesioangulation of the second molar mandibular. This information had been inserted in a spreadsheet and compared with the prevalence of the population in general by means of the application of the test of the Qui-square (x²). Additionally, the calculation of odds ratio was executed and the results had been considered to the level of significance of 5%. One strong association was verified between agenesis of the second premolar and agenesis of other permanent teeth, as well as with the microdontia of the superior lateral incisors and with important dental anomalies of position. The results are consistent with the hypothesis of that the dental agenesis, the microdontia and the ectopias are co-variable biological in a complex of linked genetic dental anomalies.